Implementasi Diplomasi Kebudayaan : Festival Nasional Reog Ponorogo Melalui Kharisma Event Nusantara 2025 (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to analyze cultural diplomacy strategies implemented through the local performing art of Reog Ponorogo as a soft-power diplomacy instrument of East Java on the international stage. Reog Ponorogo, as one of the most prominent cultural heritages of East Java, has gained global attention and plays an important role in promoting Indonesia’s cultural identity. This research focuses on the implementation of the Kharisma Event Nusantara (KEN) 2025 program by the East Java Provincial Office of Culture and Tourism (DISBUDPAR) as the main framework for cultural diplomacy. The research problems address three key aspects: how the implementation strategy of KEN 2025 can position Reog Ponorogo as an instrument of Indonesia’s cultural diplomacy; what supporting and inhibiting factors influence the execution of KEN 2025 in elevating Reog Ponorogo at the international level; and what impacts these efforts generate for strengthening Indonesia’s cultural diplomacy. A descriptive qualitative method was applied through literature studies, in-depth interviews with DISBUDPAR officials and related art practitioners, and analysis of relevant documents and data concerning the history, development, and event implementation of Reog Ponorogo. The findings indicate that the KEN 2025 program significantly contributes to strengthening the international presence of Reog Ponorogo through structured cultural promotion, enhanced interagency collaboration, and the reinforcement of East Java’s cultural identity as part of national diplomacy. The study concludes that Reog Ponorogo holds considerable potential as a cultural diplomacy instrument, and its results may serve as a reference for developing strategies for other local cultural heritage and for advancing Indonesia’s cultural diplomacy in the future.